FINANCIAL BEHAVIOR: IS IT INFLUENCED BY HEDONIC LIFESTYLE AND FINANCIAL LITERACY? (Case Study on Students of the Faculty of Economics and Business YPPI Rembang University) - Sari, Dian Anita; Ulum, Thoriqul (Universitas PGRI Semarang, 2023)
The development of market places and digital finance has a negative effect on young people's finances, especially on their financial behavior. This study aims to prove the effect of hedonic lifestyle and financial literacy on financial behavior by taking the location and respondents of students of the Faculty of Economics and Business, YPPI Rembang University. Students in the 2019-2022 batch were used as a population with a proportionate stratified random sampling technique with a total sample of 150 students. The data analysis technique uses multiple linear analysis using SPSS software. The results showed that a hedonic lifestyle has a significant positive effect on financial behavior, while financial literacy has an insignificant positive effect on financial behavior.Â